The Evolution of Blue Carbon Science - Duarte de Paula Costa, Micheli; Macreadie, Peter I. (Wetlands (Wilmington, N.C.), 2022)
‘Blue carbon’ was coined over a decade ago to describe the contribution of mangroves, seagrasses, and tidal marshes to carbon drawdown in coasts and oceans, concomitantly attracting attention of policy-makers and resource managers to their potential as a natural climate solution. Here, we explore the emergence and evolution of this relatively new research field through bibliometrics approaches to investigate patterns and trends in scientific publications through time. Our aim was to understand the evolution of blue carbon science, from where we came from and where we are now. We analysed 1,729 papers from 5,763 authors. Overall, the carbon-sink capacity of these ecosystems has been recognised long before the term ‘blue carbon’ was coined; with an annual percentage growth rate of 20% y − 1 . Research attention was highest for mangroves (~ 38% of publications), followed by saltmarshes (~ 22%), and seagrasses (~ 18%); while ~ 16% of the studies included two or more blue carbon ecosystems and 5% of the studies focused on other ecosystems. The citation burst analysis showed that, in the 1990s, the hot topic (i.e., fast-growing topic) was related to the overall flux and dynamics of carbon, with a recent transition to the role of coastal vegetation to climate change mitigation from 2009. The term ‘blue carbon’ became a hot topic in 2017, with the strongest citation burst between 2017 and 2020. This bibliometric study draws the patterns and trends of blue carbon science and indicate that this field is evolving through time to focus more on the blue carbon role as nature climate solutions.